DigiDes dan Reorientasi Tata Kelola Pemerintahan Desa Menuju Pelayanan Publik Digital yang Inklusif di Indonesia - Judy de Fretes; Muhtar Muhtar; Syamsul Bahri Abdul Rasyid (Jurnal Ilmu Sosial dan Humaniora, 2026)
This article aims to analyze the role of DigiDes in reorienting village government governance toward inclusive digital public services in Indonesia. This study employs a descriptive qualitative approach with a conceptual literature-based design. The data were obtained from journal articles, official documents, statistical publications, and institutional sources relevant to the digital transformation of village governance. The findings show that DigiDes functions not only as a village administrative application but also as an institutional instrument for strengthening data governance, service efficiency, information transparency, accountability, responsiveness, and citizen participation. However, the success of DigiDes is not automatic, as it is strongly influenced by the capacity of village officials, consistency in system use, data quality, digital infrastructure, financial sustainability, community digital literacy, and personal data protection. This article emphasizes that village digital public services must be developed inclusively to prevent the emergence of new inequalities among vulnerable groups, including older adults, low-income communities, persons with disabilities, and residents with limited internet access. The novelty of this article lies in positioning DigiDes as an instrument for reorienting village government governance, rather than merely as a technical innovation in administrative services.